Consulting 'Dr. Google' for minimally invasive urological oncological surgeries: A contemporary web‐based trend analysis. Issue 4 (5th March 2021) - Cacciamani, Giovanni E.; Sebben, Marco; Tafuri, Alessandro; Nassiri, Nima; Cocci, Andrea; Russo, Giorgio I; Hung, Andrew; de Castro Abreu, Andre Luis; Gill, Inderbir S.; Artibani, Walter
ABSTRACT: PURPOSE: To determine web‐based public interest in minimally invasive surgery (MIS) specifically for urological oncological surgical procedures and how interest in robotics and laparoscopy compares over time. MATERIALS AND METHODS: Worldwide search‐engine trend analysis included electronic Google queries of MIS urologic options from January 2004 to August 2019, worldwide. Join‐point regression was performed. Comparison of annual relative search volume (ARSV) and average annual percentage change (AAPC) were analysed to assess loss or gain of interest. Evaluations were made regarding 1) penetrance of interest for MIS in Urology; 2) how MIS urologic procedures compared over time; and 3) which were the top related queries to searches for urologic oncology procedures. RESULTS: Increased interest was found for all of the MIS procedures evaluated. Mean ARSV for robotic approach was higher for the search term 'prostatectomy" (44.8 vs. 13.5; p  < 0.001) and 'partial nephrectomy" (27.1 vs.11.5; p  = 0.02). No statistical difference was found for the search terms 'cystectomy" or 'nephrectomy". The analysis of mean (∆‐ARSV) of MIS procedures measured between the first and last 12 months of the study period showed an increased interest with a more pronounced ∆‐ARSV for robotic procedures. The top related searches for all surgical procedures were examined showing an increasing inquisitiveness with regards of type of urological cancers, treatment options, type of surgery and prognostic outcomes. CONCLUSIONS: People are increasingly searching the web for MIS urological procedures. A growing appeal for robotics is demonstrated, especially for prostatectomy and partial nephrectomy where the robotic approach is gaining traction, suggesting a shift in mind‐set amongst people seeking urological healthcare information.